- #1

- 7

- 0

## Main Question or Discussion Point

Can someone fill in the blank between these two steps? I can't find fourier series proof anywhere and my professor just left it out.

(1) y(t+nT)=y(t)

(2) y(t)=[tex]A_{0}[/tex] + [tex]\Sigma^{\infty}_{n=1}[/tex][[tex]A_{n}[/tex]cos(n[tex]\omega[/tex]t) + [tex]B_{n}[/tex]sin(n[tex]\omega[/tex]t)]

(The omega is going crazy on me... it's not supposed to be superscripted, just multiplied by n and t)

(1) y(t+nT)=y(t)

(2) y(t)=[tex]A_{0}[/tex] + [tex]\Sigma^{\infty}_{n=1}[/tex][[tex]A_{n}[/tex]cos(n[tex]\omega[/tex]t) + [tex]B_{n}[/tex]sin(n[tex]\omega[/tex]t)]

(The omega is going crazy on me... it's not supposed to be superscripted, just multiplied by n and t)